2007
DOI: 10.1111/j.1440-1819.2007.01695.x
|View full text |Cite
|
Sign up to set email alerts
|

Prolongation of P300 latency is associated with the duration of illness in male schizophrenia patients

Abstract: The association of P300 components with age, illness duration and gender were examined in schizophrenia patients and whether such variables indicate a progressive course. A total of 60 patients with schizophrenia and 70 healthy controls were studied utilizing standard auditory oddball tasks. Both healthy and schizophrenia groups had a significant positive correlation between age and P300 latency. There was also a significant positive correlation between illness duration and P300 latency in the schizophrenia gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 44 publications
(77 reference statements)
1
4
0
Order By: Relevance
“…Although we did not find any difference in pP3a and dP3a across different stages of the disease, our study showed a trend of P3a amplitude reduction in the group with the highest illness duration. These results are in line with previous studies which demonstrated that P3 amplitude is reduced in patients with longer illness duration [110,111,115,116]. Therefore, these findings suggest that P3, reflecting early attention-mediated auditory processing, might represent a marker of illness progression.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although we did not find any difference in pP3a and dP3a across different stages of the disease, our study showed a trend of P3a amplitude reduction in the group with the highest illness duration. These results are in line with previous studies which demonstrated that P3 amplitude is reduced in patients with longer illness duration [110,111,115,116]. Therefore, these findings suggest that P3, reflecting early attention-mediated auditory processing, might represent a marker of illness progression.…”
Section: Discussionsupporting
confidence: 92%
“…In fact, this ERP reflects early attention-mediated auditory processing, and consistent deficits of this index have been detected in subjects with schizophrenia [109][110][111][112][113] since the early stage of the disorder [90,114]. It has been demonstrated that P3 amplitude and latency are, respectively, decreased and delayed in patients with longer illness duration [110,111,115,116]. However, similar to MMN, the reduction in P3 amplitude is not specific of schizophrenia, as it can also be observed in other conditions, such as bipolar disorder and schizoaffective disorder [89,105,117].…”
Section: Introductionmentioning
confidence: 58%
“…Further, other studies [ 34 , 35 , 56 ] used patients who were treated with antipsychotic drugs, while our study concerned only antipsychotic-free patients. The discrepancy in presence/absence of prolonged P300 latency between a previous study [ 33 ] that also used antipsychotic-free patients and the current one may be explained by the difference in demographic data, such as age, a factor known to prolong P300 latency [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 72%
“…While ageing and task difficulty are known to influence P300 performance, especially its latency (Mori et al, 2007;Polich, 1996); demographic confounders are unlikely to explain our findings and all analyses were adjusted for age and sex. Use of cannabis and other drugs is a known risk factor for psychosis (Arseneault et al, 2004) and since the at-risk group reported recreational drug consumption more often than the controls this could have contributed to our findings.…”
Section: Discussionmentioning
confidence: 87%